Cellulose Nanomaterials in Interfacial Evaporators for Desalination: A "Natural" Choice. Issue 28 (14th June 2020) - Cao, Sisi; Rathi, Priya; Wu, Xuanhao; Ghim, Deoukchen; Jun, Young‐Shin; Singamaneni, Srikanth
Abstract: Herein, the recent advances in realizing highly efficient cellulose‐based solar evaporators for alleviating the global water crisis are summarized. Fresh water scarcity is one of the most threatening issues for sustainable development. Solar steam generation, which harnesses the abundant sunlight, has been recognized as a sustainable approach to harvest fresh water. In contrast to synthetic polymeric materials that can pose serious negative environmental impacts, cellulose‐based materials, owing to their biocompatibility, renewability, and sustainability, are highly attractive for realizing solar steam generators. The molecular and macromolecular features of cellulose and the physicochemical properties of extracted cellulose nanoparticles (cellulose nanocrystals and cellulose nanofibrils (CNF)) and natural cellulose materials (wood and bacterial nanocellulose (BNC)) that make them attractive as supporting substrate materials in solar steam generators are briefly discussed. Recent progress in designing highly efficient cellulose‐based solar evaporators, including utilizing extracted cellulose nanoparticles via bottom‐up assembly CNF, natural cellulose materials with intrinsic hierarchical structure (wood and BNC), and commercial planar cellulose substrates (air‐laid paper, cellulose paper, and cotton fabric) is reviewed. The outstanding challenges that need to be addressed for these materials and devices to be utilized in the real‐world and in overcoming global water crisis are also briefly highlighted. Abstract : Owing to their biocompatibility, renewability, and sustainability, cellulose nanomaterials are highly attractive supporting substrate materials in solar evaporators for sustainable desalination. The physiochemical properties of extracted cellulose nanoparticles and natural cellulose are discussed, and recent progress in utilizing cellulose‐based materials such as wood, bacterial nanocellulose, cellulose nanofibrils, air‐laid paper, cellulose paper, and cotton fabric in solar desalination is summarized.